2001
DOI: 10.1074/jbc.m009481200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-5-mediated Allergic Airway Inflammation Inhibits the Human Surfactant Protein C Promoter in Transgenic Mice

Abstract: Allergen challenge in the lung of humans and animals is associated with surfactant dysfunction, but the mechanism of this effect has not been established. By using a murine model of asthma we now report the effect of allergen-induced airway inflammation on the expression of transgenes regulated by the human surfactant protein (hSP)-C promoter. The hSP-C 3.7-kilobase pair promoter was used to direct the expression of eotaxin, an eosinophil-selective chemokine, into the lungs of several transgenic lines. As expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 44 publications
3
41
0
Order By: Relevance
“…However, the expression of eotaxin is not sufficient for eosinophil trafficking, as exemplified by readily detectable eotaxin in the esophagus despite the absence of eosinophils from this gastrointestinal segment (5). In addition, although eotaxin is an allergen-induced gene product in the lungs and contributes to antigen-induced pulmonary eosinophil recruitment (26,45), we have found that transgenic overexpression of eotaxin in the lung does not promote eosinophil accumulation (6). It was thus critical to generate Fabpi-eotaxin transgenic mice to determine the consequences of eotaxin overexpression in the mucosal tissue where our previous data had suggested a dominant role for this chemokine (45).…”
Section: Generation Of Fabpi Eotaxin and Il-5 Transgenic Mice-mentioning
confidence: 93%
See 1 more Smart Citation
“…However, the expression of eotaxin is not sufficient for eosinophil trafficking, as exemplified by readily detectable eotaxin in the esophagus despite the absence of eosinophils from this gastrointestinal segment (5). In addition, although eotaxin is an allergen-induced gene product in the lungs and contributes to antigen-induced pulmonary eosinophil recruitment (26,45), we have found that transgenic overexpression of eotaxin in the lung does not promote eosinophil accumulation (6). It was thus critical to generate Fabpi-eotaxin transgenic mice to determine the consequences of eotaxin overexpression in the mucosal tissue where our previous data had suggested a dominant role for this chemokine (45).…”
Section: Generation Of Fabpi Eotaxin and Il-5 Transgenic Mice-mentioning
confidence: 93%
“…These studies have revealed that eosinophils normally reside in the lamina propria of the stomach and intestine and that their base-line level is regulated by eotaxin, an eosinophilselective chemokine (4,5). However, the constitutive expression of eotaxin is not sufficient for tissue eosinophil trafficking, because some gastrointestinal segments (such as the tongue and esophagus) express eotaxin but are normally devoid of eosinophils and eotaxin-lung transgenic mice do no have elevated levels of pulmonary eosinophils (5,6). This may be explained in part by the cooperation of eotaxin with the eosinophilopoietin interleukin (IL) 1 -5, a cytokine that promotes eosinophil growth, development, survival, and responsiveness to chemoattractants (7,8).…”
mentioning
confidence: 99%
“…Mice were treated twice by intraperitoneal injection with 100 µg ovalbumin (OVA, Sigma, grade V) and 1 mg aluminum hydroxide (alum) followed by two intranasal treatments, 3 days apart, with either 50 µg OVA or saline, starting at least 10 days after the second sensitization, as previously described (Mishra et al, 2001). Mice were killed 18 hours after the second intranasal administration.…”
Section: Animal Husbandry and Doxycycline Administrationmentioning
confidence: 99%
“…A mouse model of allergic lung disease was established as described previously (36). In brief, mice were sensitized by i.p.…”
Section: Ova-induced Model Of Pulmonary Inflammationmentioning
confidence: 99%
“…The murine eotaxin-1 ELISA was used as described previously (36). The murine eotaxin-2 ELISA was a newly developed sandwich-type ELISA with custom and commercial antisera.…”
Section: Elisa Measurementsmentioning
confidence: 99%